Intestinal permeability marker zonulin as a predictor of sarcopenia in chronic obstructive pulmonary disease. (November 2021) - Karim, Asima; Muhammad, Tahir; Ustrana, Shahjahan; Qaisar, Rizwan
Abstract: Purpose: Sarcopenia or age-related muscle loss is a common finding in patients with chronic obstructive pulmonary disease (COPD) and may lead to functional compromise. The contribution of an increased gut permeability to muscle decline in COPD may be of primary relevance. We measured the plasma zonulin levels (a marker of intestinal permeability) as potential predictors of sarcopenia in COPD patients during pulmonary rehabilitation (PR). Method: We recruited male, 56–73 years healthy controls and patients with COPD (N = 70–76/group) to measure plasma zonulin, handgrip strength (HGS), body composition and biochemical parameters. All measurements were performed before and one year following the PR. Results: COPD patients had elevated plasma zonulin levels at baseline (22.8% higher vs healthy controls, p < 0.05), which were partially reduced (12.1% reduction vs baseline, p < 0.05) with PR. PR also resulted in improved HGS (8.5% increase, p < 0.05) as well as plasma c-reactive protein (CRP) (11.1% reduction, p < 0.05) and 8-isoprostanes (22.1% reduction, p < 0.05) as markers of inflammation and oxidative stress, respectively. Simple regression analysis revealed dynamic correlations of the alterations in zonulin levels with HGS, CRP and 8-isoprostanes during PR (all p < 0.05). These changes were associated with a reduction in sarcopenia incidence following PR. Conclusion: Altogether, increased intestinal permeability may contribute to muscle decline in COPD, which is partially restored by PR. Plasma zonulin may be a useful marker to evaluate sarcopenia phenotype in COPD. Highlights: Age-related muscle loss, or sarcopenia is common finding in COPD patients. COPD patients present with higher plasma zonulin levels than controls. Pulmonary rehabilitation reduced plasma zonulin and sarcopenia phenotype in COPD. Plasma zonulin is a potential marker of sarcopenia in COPD.